2022
DOI: 10.1017/jmo.2022.70
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing corporate activism: a consumer approach

Abstract: Defending social and political positions other than those that a company's clients might support has always been an avoidable risk. However, this practice, called ‘corporate activism,’ has gradually been integrated into the strategies of organizations. The object of this work is thus to understand the antecedents of corporate activism from the consumer's point of view. To understand this, we carry out structural equation modeling (SEM) based on a sample of 1,521 consumers. The results demonstrate that: (i) ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In summary, previous empirical literature has focused on the relationship between corporate activism and purchase intention (Corcoran et al, 2016;Krebel Chang, 2017;Overton et al, 2021;Robinson et al, 2012), changes in consumer attitudes (Atanga et al, 2022;Parcha & Kingsley Westerman, 2020), the impact on brand equity (Korschun et al, 2019;Vredenburg et al, 2020), reputation (Den-Hond et al, 2014), or both (Villagra, Clemente-Mediavilla, et al, 2021), as well as understanding the antecedents of the concept (institutional and corporate credibility and authenticity) from the consumer's point of view (Villagra et al, 2022). Moreover, the relationship between corporate activism and financial performance is receiving research attention (Bhagwat et al, 2020;Dodd, 2018;Dodd & Supa, 2014;Glambosky & Peterburgsky, 2022;Villagra, Monfort, & Méndez-Suárez, 2021;Weinzimmer & Esken, 2016), which is closely related to the principal objective of this research.…”
Section: Principles Of Corporate Activismmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, previous empirical literature has focused on the relationship between corporate activism and purchase intention (Corcoran et al, 2016;Krebel Chang, 2017;Overton et al, 2021;Robinson et al, 2012), changes in consumer attitudes (Atanga et al, 2022;Parcha & Kingsley Westerman, 2020), the impact on brand equity (Korschun et al, 2019;Vredenburg et al, 2020), reputation (Den-Hond et al, 2014), or both (Villagra, Clemente-Mediavilla, et al, 2021), as well as understanding the antecedents of the concept (institutional and corporate credibility and authenticity) from the consumer's point of view (Villagra et al, 2022). Moreover, the relationship between corporate activism and financial performance is receiving research attention (Bhagwat et al, 2020;Dodd, 2018;Dodd & Supa, 2014;Glambosky & Peterburgsky, 2022;Villagra, Monfort, & Méndez-Suárez, 2021;Weinzimmer & Esken, 2016), which is closely related to the principal objective of this research.…”
Section: Principles Of Corporate Activismmentioning
confidence: 99%
“…On the other hand, Villagra et al (2022) used a sample of 1,521 consumers to propose a theoretical model on the antecedents of corporate activism; these authors showed that institutional and corporate credibility and authenticity act as antecedents of this phenomenon, thus conditioning and explaining which circumstances contribute to the use of corporate activism. They also found that the higher the perceived credibility and authenticity of companies, the more positively their corporate activism actions will be regarded.…”
Section: The Relationship Between Corporate Activism and Firm Perform...mentioning
confidence: 99%
See 1 more Smart Citation